(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research intends to develop tourist technological capabilities leading to improving total performance of the tourism sector or tourist organization by depending on the compatibility of the type of technology with the source of equipment. The research was conducted on a group of tourist formations in Basra Governorate. Two checklists were used for data collection purposes, one on the general importance of tourism, and one on the conceptual model. The research reached a set of results, the most important of which is the role that tourism technology plays in improving technological capabilities that lead to improving the overall performance of the tourism sector.